Sborník historicky. [Sv.] 11-13. [Věd. red.: J.Křížek] (Nakladatelství Československé Akademie věd.)
Československá Akademie věd. 11. [Aut.: Zd. Šimeček, J. Purš, J. Doležal a j.]. 1963. 295 s. - S mp. a tab.